2021
DOI: 10.1017/s095457942100122x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal pathways between emotional difficulties and school absenteeism in middle childhood: Evidence from developmental cascades

Abstract: Emotional difficulties are associated with both authorized and unauthorized school absence, but there has been little longitudinal research and the temporal nature of these associations remains unclear. This study presents three-wave random-intercepts panel models of longitudinal reciprocal relationships between teacher-reported emotional difficulties and authorized and unauthorized school absence in 2,542 English children aged 6 to 9 years old at baseline, who were followed-up annually. Minor differences in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The programme aimed to explore and test new ways to improve the mental health and wellbeing of young people aged 10 to 16 and prevent serious mental health issues from developing. Considering the impact of mental health difficulties on absenteeism ( Panayiotou, Finning, Hennessey, Ford & Humphrey, 2021 ) and academic attainment ( Deighton et al., 2018 ; Panayiotou & Humphrey, 2018 ), by improving mental health and wellbeing of young people, the programme also aimed to increase academic outcomes over the long-term.…”
Section: Background On the Headstart Programmementioning
confidence: 99%
“…The programme aimed to explore and test new ways to improve the mental health and wellbeing of young people aged 10 to 16 and prevent serious mental health issues from developing. Considering the impact of mental health difficulties on absenteeism ( Panayiotou, Finning, Hennessey, Ford & Humphrey, 2021 ) and academic attainment ( Deighton et al., 2018 ; Panayiotou & Humphrey, 2018 ), by improving mental health and wellbeing of young people, the programme also aimed to increase academic outcomes over the long-term.…”
Section: Background On the Headstart Programmementioning
confidence: 99%
“…Such studies have revealed patterns as children move from preschool to elementary school (e.g., lower levels of school readiness to chronic absenteeism; Ehrlich et al, 2018); from elementary school to middle school (e.g., increased school disengagement and declining grades to absenteeism; Schoenberger, 2012); and from middle school to high school (e.g., increased psychopathology to absenteeism; Wood et al, 2017). Others have examined longitudinal patterns for SA/Ps with respect to disabilities, emotional difficulties, and academic achievement, among other variables (e.g., Chen et al, 2016;Smerillo et al, 2018;Panayiotou et al, 2021). In addition, application of an ecological system model to SA/Ps has burgeoned in recent years.…”
Section: Postmodern Dimensionsmentioning
confidence: 99%
“…Exposure to instructional time benefits intellectual development, academic achievement, and educational outcomes ( Allensworth & Balfanz, 2019 ; Ginsburg et al, 2014 ; Keppens & Spruyt, 2020 ). Positive health outcomes are allegedly influenced by the roles youths can have at school ( Bonell et al, 2019 ) and by the social, emotional, and academic functioning they develop during the school years ( Okano et al, 2019 ; Panayiotou et al, 2021 ). Depending on the curriculum, school attendance can influence identity, passions, morals, and ethics ( Eccles & Roeser, 2011 ).…”
Section: The Advantages Of School Attendancementioning
confidence: 99%